2022
DOI: 10.3390/brainsci12050579
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chronological Age in Healthy Elderly Subjects with Machine Learning from MRI Brain Segmentation and Cortical Parcellation

Abstract: Normal aging is associated with changes in volumetric indices of brain atrophy. A quantitative understanding of age-related brain changes can shed light on successful aging. To investigate the effect of age on global and regional brain volumes and cortical thickness, 3514 magnetic resonance imaging scans were analyzed using automated brain segmentation and parcellation methods in elderly healthy individuals (69–88 years of age). The machine learning algorithm extreme gradient boosting (XGBoost) achieved a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The dataset used here came from a single-centre, observational cohort study of 1213 subjects [ 29 , 34 , 35 ]. The participants were home-dwelling elderly volunteers, aged 69 to 85, without relevant psychiatric, neurological, or systemic disorders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset used here came from a single-centre, observational cohort study of 1213 subjects [ 29 , 34 , 35 ]. The participants were home-dwelling elderly volunteers, aged 69 to 85, without relevant psychiatric, neurological, or systemic disorders.…”
Section: Methodsmentioning
confidence: 99%
“…In the machine-learning literature, brain age is understood as the model estimate to be compared with the given or chronological age [ 29 ]. However, this approach depends on the model’s capacity to accurately predict the brain’s biological age.…”
Section: Introductionmentioning
confidence: 99%
“…The authors indicated that the cortical thickness in temporal parietal lobes exhibited better prediction accuracy than frontal and occipital lobes. Additionally, they suggested that integrating the prediction model and interpretation process could help to reduce the gap between chronological and real brain age [16].…”
Section: Introductionmentioning
confidence: 99%
“…Gómez-Ramírez et al [ 15 ] applied machine learning from Magnetic Resonance Imaging (MRI) brain segmentation and cortical parcellation to assess age-related brain changes in normal brain aging. They found brain-to-intracranial-volume ratio to be the most significant aspect in predicting age, followed by hippocampal volume, and discovered cortical thickness in temporal and parietal lobes to be more predictive than frontal and occipital lobes.…”
mentioning
confidence: 99%